Angiotensin II and the Renal Hemodynamic Response to an Isolated Increased Renal Venous Pressure in Rats - Huang, Xiaohua; Hamza, Shereen M.; Zhuang, Wenqing; Cupples, William A.; Braam, Branko (Frontiers in Physiology, 2021)
Elevated central venous pressure increases renal venous pressure (RVP) which can affect kidney function. We previously demonstrated that increased RVP reduces renal blood flow (RBF), glomerular filtration rate (GFR), and renal vascular conductance (RVC). We now investigate whether the RAS and RBF autoregulation are involved in the renal hemodynamic response to increased RVP. Angiotensin II (ANG II) levels were clamped by infusion of ANG II after administration of an angiotensin-converting enzyme (ACE) inhibitor in male Lewis rats. This did not prevent the decrease in ipsilateral RBF (−1.9±0.4ml/min, p<0.05) and GFR (−0.77±0.18ml/min, p<0.05) upon increased RVP; however, it prevented the reduction in RVC entirely. Systemically, the RVP-induced decline in mean arterial pressure (MAP) was more pronounced in ANG II clamped animals vs. controls (−22.4±4.1 vs. −9.9±2.3mmHg, p<0.05), whereas the decrease in heart rate (HR) was less (−5±6bpm vs. −23±4bpm, p<0.05). In animals given vasopressin to maintain a comparable MAP after ACE inhibition (ACEi), increased RVP did not impact MAP and HR. RVC also did not change (0.018±0.008ml/minˑmmHg), and the reduction of GFR was no longer significant (−0.54±0.15ml/min). Furthermore, RBF autoregulation remained intact and was reset to a lower level when RVP was increased. In conclusion, RVP-induced renal vasoconstriction is attenuated when ANG II is clamped or inhibited. The systemic effect of increased RVP, a decrease in HR related to a mild decrease in blood pressure, is attenuated also during ANG II clamp. Last, RBF autoregulation remains intact when RVP is elevated and is reduced to lower levels of RBF. This suggests that in venous congestion, the intact RBF autoregulation could be partially responsible for the vasoconstriction.